Pengaruh Model Pembelajaran Teams Games Tournament Terhadap Hasil Belajar Siswa Kelas III Sekolah Dasar - Hakim, Shafira Bonita; Jannah, Ana Naimatul (Yayasan Arrahman Nahdlatul Wathan, 2024)
This study aims to determine the effect of the Teams Games Tournament (TGT) learning model on student learning outcomes in theme 5 sub-themes 1 at third grade of Elementary School of Kamal 1. This research is a quantitative research with experimental research type, the design used is Pre-Experimental Designs with One-Group Pre-test-Post-test Design. Sampling using sample population technique. The sample used amounted to 26 students. Data was collected using pre-test and post-test questions. The results of the study show that the Teams Games Tournament (TGT) learning model has a significant effect on student learning outcomes. The effect of the difference is evident from the results of the paired sample t-test. The results of the calculation of the paired sample t-test obtained a significance value of 0.000. Since the value of Sig. (2-tailed) < 0.05 (0.000 < 0.05), and the t-count value is greater than t-table (28.257 > 2.160) then H0 is rejected and Ha is accepted, which means that there is a significant influence on the application of the Teams Games Tournament (TGT) learning model on student learning outcomes in theme 5 sub-theme 1 at third grade of Elementary School of Kamal 1.